Living with Stigma: Depressed Elderly Persons' Experiences of Physical Health Problems - Anne Lise Holm; Anne Lyberg; Elisabeth Severinsson (Hindawi Limited, 2014)
The aim of this paper is to deepen the understanding of depressed elderly persons' lived experiences of physical health problems. Individual in-depth interviews were conducted with 15 depressed elderly persons who suffer from physical health problems. A hermeneutic analysis was performed, yielding one main theme, living with stigma, and three themes: longing to be taken seriously, being uncertain about whether the pain is physical or mental, and a sense of living in a war zone. The second theme comprised two subthemes, feeling like a stranger and feeling dizzy, while the third had one subtheme: afraid of being helpless and dependent on others. Stigma deprives individuals of their dignity and reinforces destructive patterns of isolation and hopelessness. Nurses should provide information in a sensitive way and try to avoid diagnostic overshadowing. Effective training programmes and procedures need to be developed with more focus on how to handle depressive ill health and physical problems in older people.